Toxoplasmosis of Goat and Sheep in Java - Iskandar, Tolibin (Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
Toxoplasmosis is a parasitic disease, caused by Toxoplasma gondii attacking goat, sheep, and wild animals. This disease is zoonosis and widely distributed in many districts of Java and as a zoonotic disease. Cat is the definitive host of T. gondii, while sheep, goats, and humans are the intermediate hosts. The prevalence of toxoplasmosis in Java was between 7 to 84%, with an average of 42.9%. It occurs through out of the year and causes abortions and infertilities of infected animals. All breeds of goat and sheep, male and female are susceptible to T. gondii infections. In cat, T. gondii produces three types of infectious forms, i.e.: tropozoite, cyst, and oocyst, but in intermediate host, it produces tropozoite and cyst forms. The development of T. gondii in definitive host is by sexual and asexual, while in intermediate host only by asexual only. Toxoplasmosis in livestocks is subclinical signs and difficult to diagnose. The confirmation diagnose of T. gondii infection in animals should be conducted by laboratory examinations of the parasite on peritoneal fluid, heart muscles, skelet muscles and brain samples. Serological tests for antibody detection can be done by enzyme linked immunosorbent assays (ELISA). Toxoplasmosis is difficult to be controlled; the use of pyrimethamine drugs only kills tachyzoite form, but does not kill the cyst. Once the animals are infected, they would become carriers and sources of infections. Â  Key words: Toxoplasmosis, goat, sheep